In situ time-zero correction for a ground penetrating radar monitoring system with 3000 antennas. (1st July 2022) - Steinbeck, Leon; Mester, Achim; Zimmermann, Egon; Klotzsche, Anja; van Waasen, Stefan
Abstract: The time-zero correction is an essential step in the data pre-processing of ground penetrating radar (GPR) measurements to obtain an accurate signal propagation time between transmitting and receiving antennas. For a novel custom GPR monitoring system with about 3000 antennas and corresponding transceiver structures placed around a soil sample (lysimeter), an in situ approach for the time-zero correction is required. In particular, unknown material properties between any pair of transmitting and receiving antennas prevent a conventional time-zero correction. We present and compare two calibration approaches, namely a pairwise and a mesh calibration, both utilizing the ability of the monitoring system to conduct reciprocal measurements between any pair of antennas. The pairwise calibration enables an individual calibration for any antenna pair, whereas the mesh calibration reduces the influence of the soil between antenna pairs compared to the pairwise calibration. The developed approach is verified by utilizing a mathematical model. Experimental results from a simplified setup show that the lysimeter filling has a negligible impact onto the calibration approach based on adjacent measurements for the mesh calibration. In addition, it is shown that a state of the art time-zero calibration can be used to measure the signal delays within the analog circuit of the measurement system with an accuracy of ±4 ps. The simulation results indicate that by using the developed concept, no prior air calibration between every possible antenna combination is necessary. Thus, this work provides a crucial contribution towards an automated in situ time-zero correction for 3D GPR monitoring systems with many antennas.